Leveraging Corporate Venture Capital for Customer-Centric Innovation in the Hospitality Industry - Shreeram Iyer, Nisha Bamel, Mohd Akbar Ansari (European Economic Letters (EEL), 2024)
In the current competitive hospitality landscape, corporate hotels are under increasing pressure to meet rising customer expectations while also facing competition from disruptive startups. To address these challenges, this paper explores the potential benefits of Corporate Venture Capital (CVC) as a strategic tool for corporate hotels to partner with startups and enhance their customer experience. It is believed that CVC offers unique advantages over traditional investment, such as early access to emerging technologies and innovative business models. By collaborating with startups, hotels can experiment with and integrate innovative solutions into their offerings before they become widely adopted. Furthermore, partnering with startups can provide hotels with valuable insights into evolving customer preferences and behaviors, enabling them to create personalized and data-driven experiences. Startups also offer hotels an agile and experimental approach, allowing them to test new concepts and adapt quickly to changing market trends. CVC collaborations can also create a unique value proposition for hotels, highlighting their commitment to innovation and customer-centricity. This paper proposes a framework for effective CVC-driven collaboration between corporate hotels and startups, which includes key considerations such as defining objectives and aligning on mutual goals, establishing clear communication channels, developing a flexible and adaptive partnership model, and managing risks and addressing potential conflicts of interest. The research aims to provide practical insights for corporate hotels to leverage the power of CVC to drive customer-centric innovation and gain a competitive edge in the dynamic hospitality landscape.